(untitled) (Journal of the College of Basic Education, 2022)
This research aims to know the level of using inferential thinking skills for fourth-grade literary students in the subject of Arabic language. In order to achieve the goal of the research, inferential thinking skills must be identified, including: Deduction: Deduction is the method of drawing a particular conclusion based on a theory or law, and it can be used to switch from one general problem to another. It is the polar opposite of induction. Induction: it is the process of analyzing evidence and partial events, as well as the extremism that results from this, in order to arrive at a general opinion that applies to all of them and has an effect on all of them. and begins with the pieces before moving on to the general and general provisions.The researcher used a descriptive approach, which entailed first identifying the overall study population, which consisted of(960) day preparatory school students in Karbala Governorate, and then selecting a research sample from that community using a simple random process, which totaled(220) students. So it consisted of (30) multiple choice objective paragraphs distributed on induction and induction skills, and I returned for this reason, and the tool’s validity and stability were verified, and after the test took its final form, the researcher applied it to the research sample, If the application period lasted from (1/6/2021/7/2 / 2021AD), the researcher unpacked and corrected the test results, and measured his scores using the response key assigned to him after the application period ended.The findings revealed that the study sample has a high degree of inferential thought. The researcher came to some conclusions, one of which is that the participants of the study sample obviously have the capacity to think inferentially.In terms of the researcher’s recommendations, they are as follow: The importance of inferential thought skills in the preparatory stage of Arabic language teaching. Attention and care for the development or formation of inferential thought skills in Arabic language branches. The need for Arabic language teachers to be educated in critical thought skills and "metacognitive" skills in order to keep up with science and literary developments. The researcher reached several proposals, including: Conducting a study similar to the current research on students of the Open Education College. Preparing a training program to develop inferential thinking skills among literary fourth-grade students.